Permainan Lompat Kanguru Untuk Meningkatkan Hasil Belajar Lompat Jauh Gaya Jongkok (Department of Physical Education, Sport, Health and Recreation, 2015)
This research aims to know the effectiveness of learning long jump squat-style through a kangaroo jump play approach for students of class IV SD Negeri Bangungalih Tegal Regency Kramat District 02 This type of research is the Research Action class Research is carried out in SD Negeri Bangungalih Kecamatan Tegal Regency Kramat 02, subject of research grade IV with 48 students, consisting of 20 men and 28 students student daughter. The instruments used are observation sheet implementation of learning, learning results sheets, now students and student performance tests. Results of the research cycle 1 showed the basic motion skills reach 70.83% and yield learning long jump reached 71% of the research cycle II increased 18.75% i.e. reaching 89,58% and 71% and the results of the learning process the long jump 21% increase that reached 92%. The determination of indicators for success in learning that is 85%, so it can be concluded that the activity of students in learning is said to follow successfully. Based on the results of the research study of the long jump Kangaroo jump game approach through, can improve the learning results of long jump squat style of 70,83% to 89,58% advice from researchers teachers are expected to utilize the research results of model learning long jump squat-style through a kangaroo jump approach taking into account the situation and condition of the local environment.